Secure Communities as Immigration Enforcement: How Secure Is the Child Care Market? - Umair Ali; Jessica H. Brown; Chris M. Herbst (Institute of Labor Economics (IZA), 2022)
Immigrants comprise nearly 20% of the child care workforce in the U.S. This paper studies the impact of a major immigration enforcement policy, Secure Communities (SC), on the structure and functioning of the child care market. Relying on the staggered introduction of SC across counties between 2008 and 2014, we find that the program reduced children's participation in center-based child care programs. The estimated reductions are substantially larger among disadvantaged children, raising questions about the possibility of health and developmental spillovers. We also find that SC reduced the supply and wages of immigrant and native child care workers in the center-based sector. We provide descriptive evidence that immigrants and natives may not compete for the same jobs: immigrant child care teachers are more highly skilled, and the children assigned to their classrooms differ on some observable characteristics. Therefore, immigrants and natives are likely to be complements to child care service production.
Keywords: J13; J15; J21; K39; 330; child care; maternal employment; immigration; Secure Communities